ANALISIS KUALITAS PRODUK, PROMOSI, DAN KEBUTUHAN MENCARI VARIASI TERHADAP KEPUTUSAN PERPINDAHAN MEREK SEPEDA MOTOR YAMAHA KE MEREK SEPEDA MOTOR HONDA (Studi Pada Mahasiswa Universitas Stikubank Semarang) - Putri Nur Adila, 11.05.51.0065 (Students Journal of Economic and Management, 2015)
This study was conductedtoanalyze the effect ofthe variable quality ofthe product, promotion, andthe need to find variations ofbrand switchingdecision Yamaha motorcycletomotorcycle brandHonda. Respondentsof this studyis thestudents UniversityStikubankSemarangswitch brandsYamaha motorcycletomotorcycle brandHonda totaling100 respondents. Sampelretrievaltechniqueusingpurposivesampling, thenanalyzed usinglinear regression. These results indicatethatbrand switchingdecisionpositively and significantlyinfluencedby the quality ofthe product, promotion, andthe need to findvariations. The most dominant variableaffecting thebrand switchingdecisionmotorcycle brandtobrandYamahamotorcycleHondais the quality ofthe product. Keyword: product quality, promotion, the need to find variations and brand swithcing decision